A Randomised Controlled Trial to Delay or Prevent Type 2 Diabetes after Gestational Diabetes: Walking for Exercise and Nutrition to Prevent Diabetes for You - A. S. Peacock; F. E. Bogossian; S. A. Wilkinson; K. S. Gibbons; C. Kim; H. D. McIntyre (International Journal of Endocrinology)
Aims. To develop a program to support behaviour changes for women with a history of Gestational Diabetes Mellitus (GDM) and a Body Mass Index (BMI) > 25 kg/m2 to delay or prevent Type 2 Diabetes Mellitus. Methods. Women diagnosed with GDM in the previous 6 to 24 months and BMI > 25 kg/m2 were randomized to an intervention (I) (n=16) or a control (C) (n=15) group. The intervention was a pedometer program combined with nutrition coaching, with the primary outcome increased weight loss in the intervention group. Secondary outcomes included decreased waist and hip measurements, improved insulin sensitivity and body composition, increased physical activity, and improved self-efficacy in eating behaviours. Results. Median (IQR) results were as follows: weight: I −2.5 (2.3) kg versus C +0.2 (1.6) kg (P=0.009), waist: I −3.6 (4.5) cm versus C −0.1 (3.6) cm (P=0.07), and hip: I −5.0 (3.3) cm versus C −0.2 (2.6) cm (P=0.002). There was clinical improvement in physical activity and eating behaviours and no significant changes in glucose metabolism or body composition. Conclusion. A pedometer program and nutrition coaching proved effective in supporting weight loss, waist circumference, physical activity, and eating behaviours in women with previous GDM.